The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-252660/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cost Effective Approach for Subsonic Aeroelastic Stability Analysis of Turbomachinery 3D Blade Cascade. A Reduced Order Aeroelastic Model Numerical Approach

Abstract: In this paper a cost effective numerical model for subsonic classical flutter analysis for turbomachinery is presented. The model is based on reduced order aeroelastic modeling (ROAM) approach. The prime objective of the ROAM is to significantly reduce the computational time for flutter analysis of low pressure (LP) stage blades of power turbines at preliminary design stage. A mesh free incompressible fluid solver based on boundary element method(BEM) e.g. 3D panel method is developed. The proposed ROAM is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A study of Classical flutter as shown in Fig. 1b in the 2D blade cascade using PM based BEM flow solver is carried out by Prasad et al [8,9]. In the stall flutter case, the flow is dominated by separated flow, thus classical PM can be used here.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Classical flutter as shown in Fig. 1b in the 2D blade cascade using PM based BEM flow solver is carried out by Prasad et al [8,9]. In the stall flutter case, the flow is dominated by separated flow, thus classical PM can be used here.…”
Section: Introductionmentioning
confidence: 99%